SUPPLY CHAIN MANAGEMENT PETERNAKAN BURUNG PERKUTUT BERBASIS WEBSITE (STUDI KASUS: PETERNAKAN ASMARA) - Salsa Silvadari, (2022)
Asmara Bird Farm is a turtledove farm that was founded in 1996 and has been registered with P3SI (Indonesian Perkutut Preservation Association). In asmara's farm, there is no recording of ordering or purchasing data and in processing data such as recording hatched birds still using sheets of paper owned by Asmara farmers. In this case, it can experience risks such as data loss and irregular storage, so it requires a Supply Chain Management information system to assist Asmara farmer owners in managing farms and can distribute livestock products to consumers. This system will be made website-based, using PIECES analysis and using prototype methods for system development, PHP for programming languages and MySQL as a database. Get results by creating a Supply Chain Management application on a website-based Asmara farm that makes it easier for farmers to manage their turtledove farms. Produce features for procurement of raw materials, managing production and distributing on the admin dashboard. As well as producing the feature of placing orders on customers to the delivery stage, so that with this system can see the initial process to reach the customer's hands.